Characterization of acinetobacter baumannii from hospital-adjacent waterbodies in Dhaka city - Saiyan, Zwad Al; Jahan, Afia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.